Main factors in the adoption of digital marketing in startups: A online focus group analysis - Teixeira, Sérgio (2018)
The main purpose of this paper is to help small businesses such as startups to successfully adopt and implement digital marketing as a strategy in their business plan. Given that many of these companies have a considerable number of fragile internal characteristics, such as a lack of access to financial capital while lacking also qualified human resources, they can't adopt a technology without first evaluating how it would affect them. With this in mind, this study will go through several stages of qualitative analysis to find the most relevant and important factors in the adoption of digital marketing in startups. We are looking to validate the results of each step with experts in the field; in order to do that an online focus group tool will be used so that the digital marketing specialists can propound their opinions.